TI_GERICHTE 17.2011.129 vom 21. Mai 2012 , Commisurazione della pena in caso di lesioni semplici. Negata l'applicazione dell'art. 52 CP - TI Tribunale d'appello (2012)
Commisurazione della pena in caso di lesioni semplici. Negata l'applicazione dell'art. 52 CP